TANGGUNGJAWAB RUMAH SAKIT TERHADAP PENGAMBILAN DAN PENYEBARLUASAN GAMBAR DIRI PASIEN YANG MELANGGAR KESUSILAAN - Nitro Galenso; Dian Kurniasari Yuwono (The Juris, 2023)
Prioritizing patient privacy is a characteristic of Hospital services. However, sometimes, it is violated intentionally or unintentionally. The violation act is such as taking the image of a patient in a certain unethical condition without the patient's consent. This study is a law normative study with a statuta approach, held in August 2023. It aims to analyze the laws and regulations related to the Government's responsibility to provide safety and patient privacy in hospital services. The spreading of unethical patients' self-images shows that the implementation of related laws and regulations needs to be improved. The recording/photographing of patients is the Hospital's responsibility by the Act/Law No. 17 of 2023, which points out the patient's/family's/Hospital's consent and the Health Ministerial Regulation no.24, 2016 on technical requirements for hospital buildings and infrastructure that divide privacy zones of patient service. Meanwhile, distributing/spreading unethical images of the patients through media is the responsibility of a person/party in accordance with act/law no. 19 of 2016 on the amendment to act/law no. 8 of 2008 on information and electronic transactions. If these laws and regulations were implemented optimally by all parties, the chance of recording/photographing patient in unethical conditions without their consent or violating their privacy, could be prevented. Implementations of related laws and regulations should be conducted of all parties. Regarding this matter, Hospitals’ responsibilities are providing information, education, forbidden signs, and security guarantees to the patient and their family.